Objeto transfigurado e obra de arte na contemporaneidade : Arthur Coleman Danto e Maurice Merleau-Ponty - Rogoski, Larissa Couto (2015)
This study aims to investigate the transformation of the banal object into a work of art, focusing especially on the art produced in the contemporary world. To carry out this research, the study will use the art theories of Arthur Coleman Danto and Maurice Merleau-Ponty. The method that will be used is a critical reading of philosophical works relevant to the subject, to clarify thoughts and allow connections on the topic. The author opted for a description of the theories of Danto and Merleau-Ponty, addressing their intersections and contributions to the question raised about the transfiguration of the object into a work of art. The concept of interpretation that Danto produces, along with Merleau-Ponty’s theory of perception, are some targets of the investigation. The internal coherence of the work concludes with theoretical research into the case of artistic performance, using this as a point of convergence between both theories and an experiential basis for the relevance of the questioning that the study poses. The artistic performance research focuses, for methodological purposes, on concepts of body, time, space and audience.